Pelestarian Jimpitan sebagai Upaya Pemberdayaan Masyarakat dalam Pembangunan di Kelurahan Patemon, Gunung Pati, Kota Semarang (Forum Ilmu Sosial, 2020)
The concept of community empowerment is the process of preparing the community with various resources, opportunities, knowledge, and expertise to increase the capacity of the community in determining the future, as well as participating and influencing life in the community itself. One form of community participation in RT 04 RW 01, Patemon, Gunung Pati, Semarang City in development is through a â€œjimpitanâ€ program. â€œJimpitanâ€ is a tradition of community self-help program where the community voluntarily gives money or rice to the designated officers and usually the collection time is every day in conjunction with night watch patrols. This activity is an example of a village community empowerment program, where the community has an active role in working together to collect voluntary contributions and manage and process the results in the form of physical and non-physical development in their respective areas. In addition to utilizing money from the â€œjimpitanâ€, the collection process also has a positive impact, namely improving family attitudes and mutual cooperation in the community amid the rapid development of social media, creating harmony, peace, and increasing community participation in protecting and developing the environment. The tradition of â€œjimpitanâ€ is very worth keeping because of the many positive effects it poses.